Development of a Scaleable Breath-figure Type Polymer Thin Film Patterning Process via Controlled Vapour Swelling of Thin Films - Darragh, Philip (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2023)
Efficient production of microporous polymeric films can be rapidly synthesised by changing the thermodynamics of a polymeric solution in a humid atmosphere. This conventional method, known as ?breath figure? (BF), involves drop casting a volatile polymer solution on to a flat surface and results in an evaporative cooling effect. Once the temperature of the polymer solution reaches the dew point, water droplets begin to condense on to the surface and their morphology dictates the micropore?s density and size that exist within the polymer film. The BF method has received significant attention in respect to the process creating homogenous porosity in polymer thin films in less than 5 minutes. However, the conventional method has its flaws in respect to reproducibility and defects over large surface areas. Here a new method is outlined using a customised piece of apparatus that can create various film porosity by precisely controlling and automating all variables that occur within the BF process, solvent saturation, relative humidity, temperature, and polymer type. The polymer of interest that has been studied in significant detail is polystyrene (PS), a low cost polymer that has high spin-coating thickness uniformity, process stability and functions as a dry etch resist. By swelling the PS film of uniform thickness in a favourable solvent, the viscosity can be decreased creating a viscoelastic mouldable film that can be templated by water droplets at the temperature dew point. This process can remove the problems with fluid dynamics, by controlling the swelling of the film through temperature control and the in-situ swelling can be characterised by reflectometry. This approach can allow us to understand the role of thermodynamics on water droplet templating and interpret the effects of polymer swelling on the production of the microporous materials. Using these concepts, a fast method for producing different sizes of microporous PS resists can be assessed. These templates can function as pattern-transfer templates for countless lithographic techniques and methodologies.
APPROVED